Influence of microstructure on the wettability of tobacco leaves: a theoretical model and quantitative analysis - Tie, Jinxin; Shen, Binfeng; Qiao, Yuehui; Zhao, Wei; Xu, Ronghua; Wang, Miao; Li, Kecheng; Qian, Jie (Frontiers in Materials, 2024)
Wettability has widespread applications in everyday life such as waterproof clothing, moisture-proof materials, and self-cleaning surfaces. It is also a common phenomenon observed in plants like the lotus, where superhydrophobicity is primarily influenced by chemical composition and microstructure, with the latter playing the most critical role. In this paper, we explore how microstructure affects the wettability of tobacco leaves and examine the relationship between microstructure and contact angle. We select three different Roast tobacco leaves and use Neumann models and Owens-Wendt-Rabel-Kaelble (OWRK) models to calculate the surface energy, and the surface energy is between 28 and 31 mN/m and the Young’s contact angle is around 90°. Based on the Cassie–Baxter model, we develop theoretical models of venation and foliage for predicting contact angles. The results show that the surface of the tobacco leaves can transition from hydrophilic to hydrophobic by modifying the size of the surface microstructure. Also we develop a method that use SEM and ImageJ to predict contact angle on leaves by analyzing solid-liquid contact area. The results indicate that the discrepancy between the theoretical and experimental results is within 5%. These findings may provide a better understanding of the wettability in natural plants and may pave a new way of realizing surface fabrications with specific infiltrating properties in industries.